Improving first-year intervention strategies at universities by focusing on meaning and purpose in life - Shin, Joo Yeon, author; Steger, Michael F., advisor; Dik, Bryan J., committee member; Henry, Kimberly L., committee member; Kuk, Linda, committee member (Colorado State University. Libraries, 2013)
Research has increasingly appreciated the potential benefits of having a higher sense of meaning in life for positive college student development. Drawing on Steger's (2009) meaning development model, this study investigated the effects of a 6-week web-based intervention designed to enhance a sense of meaning in life among college freshmen. The results from a randomized controlled trial with 285 U.S. college students (n = 142 for the intervention group, n = 143 for the control group) revealed that the rates of growth of meaning in life within the two groups did not differ over a period of 8 weeks. The current study also examined the relationships between self-concept clarity, goal progress, and meaning in life. Higher self-concept clarity was associated with a higher sense of meaning in life, and this relationship was found both in between-person and within-person contexts. Additionally, the changes in self-concept clarity and meaning in life were positively related over the course of 8 weeks. Higher goal progress was associated with a higher sense of meaning in life in a between-person context. Overall, these results suggest that self-knowledge and goal pursuit serve as a firm context for cultivating a sense of meaning. Finally, a higher sense of meaning was associated with reports of fewer symptoms of depression and anxiety, but not with a higher GPA and retention to sophomore year. The role of meaning in life in enhancing college students' mental health and educational experiences was discussed. Directions for future intervention efforts to promote a sense of meaning in life among college students were also suggested.
Keywords: college; purpose; meaning; first-year intervention